2023
DOI: 10.1002/jia2.26105
|View full text |Cite
|
Sign up to set email alerts
|

Integrating 3HP‐based tuberculosis preventive treatment into Zimbabwe's Fast Track HIV treatment model: experiences from a pilot study

Abstract: Introduction: Tuberculosis (TB) causes one-third of HIV-related deaths worldwide, making TB preventive treatment (TPT) a critical element of HIV programmes. Approximately 16% of people living with HIV (PLHIV) on antiretrovirals in Zimbabwe are enrolled in the Fast Track (FT) differentiated service delivery model, which includes multi-month dispensing of antiretrovirals and quarterly health facility (HF) visits. We assessed the feasibility and acceptability of utilizing FT to deliver 3HP (3 months of once-weekl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This shows that receiving support from a family member and SMS reminders was acceptable to the majority. Perceived TB risk is also reported as a facilitator for 3HP acceptance in other studies in Africa(20,21).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…This shows that receiving support from a family member and SMS reminders was acceptable to the majority. Perceived TB risk is also reported as a facilitator for 3HP acceptance in other studies in Africa(20,21).…”
Section: Discussionmentioning
confidence: 61%
“…WHO advocates use of digital technologies for attaining the End TB strategy 2035 targets(22) and studies have shown that digital technologies enhance latent TB treatment adherence and is acceptable to PLHIV(13,21,23). Reminder SMS could thus, be a good option to improve 3HP adherence and attain desired completion rate among PLHIV.…”
Section: Discussionmentioning
confidence: 99%